Knowledge, perception and experiences of primipara mothers on early breast feeding initiation in Universiti Kebangsaan Malaysia Medical Center - Mamat, Rohani (2015)
World Health Organization (WHO) and the United Nations Children's Fund (UNICEF) recommend that all infants should be exclusively early breastfed immediately within one hour post-delivery. The decision and practices to early breastfeeding initiation (BFI) are influenced by many contributing factors. It is well recognized that poor knowledge and practice of early breastfeeding is pronounced among mothers. This research was conducted to assess the predictive factors of knowledge, perceptions, practices and experiences of primipara mothers as well as its related factors towards early BFI in University Kebangsaan Malaysia Medical Centre (UKMMC). A cross-sectional descriptive study was conducted with two hundred and fifteen primiparas (n=215) in postnatal wards, UKMMC. Purposive sampling was used to recruit the sample. Data was collected using a self-administered questionnaires adapted from the Newborn Feeding Ability (NFA) and Breastfeeding Initiation Practices (BIP) after gaining ethics approval from USM and UKMMC. The questionnaires included socio-demographic data, knowledge, perceptions, practices and experiences of mothers towards early BFI. The results showed that half of the respondents (46.5%) had higher knowledge of early initiation of breastfeeding, however the majority of respondents (52.1%) revealed gaining insufficient support from the midwives to assist them in initiating early breastfeeding. There was a significant association between higher education and level of knowledge on early BFI (p=0.001). Additionally, there is a significant association between higher income and level of perceptions of early BFI (p=0. 015). It can be concluded that the mothers are still lacking in knowledge of early BFI while intentions regarding breastfeeding their infants is poor. Hence, the BFI training program for both mothers and midwives is needed. This study suggests that systematic assessment of knowledge and practice of ten steps successful breastfeeding among midwives in UKMMC should be established to evaluate their competency in supporting mothers to breastfeed infants.